First-principles investigation on the structural, electronic, mechanical and optical properties of silver based perovskite AgXCl3 (X= Ca, Sr) - Umar Ayaz Khan; Naimat Ullah Khan; Abdullah; Abdulaziz H. Alghtani; Vineet Tirth; Sara J. Ahmed; Muhammad Sajjad; Ali Algahtani; Tahir Shaheed; Abid Zaman (Journal of Materials Research and Technology, 2022)
Structural, electronic, optical and elastic properties of Silver based Perovskite AgXCl3 (X = Ca, Sr) are studied by utilizing wien2k package with in DFT. The structural investigation reveals their stability and shows that these compounds are cubic with space group pm-3m 221. For electronic properties the band structure and density of states are computed which indicates the semiconducting nature of both compounds. Elastic constants, Pugh’s ratio, bulk modulus, Poisson’s ratio and anisotropy factor are studied for the analysis of elastic characteristic. The Pugh’s ratio describes the ductile nature of the compounds and ionic nature is determined from the evaluated Cauchy pressure. Optical parameters such as dielectric function, extinction coefficient, refractive index, absorption coefficient, reflectivity and optical conductivity are calculated in the energy range of 0 eV–35 eV. The thermal stability is conformed from the thermal property. The study of these compounds reveals that they can be potential candidates for optoelectronic devices.